Non-Compete Clauses in Contracts and Antitrust Law in Indonesia - Kennedy, Alexander; Mustika, Syilfia Regita; Surya, William Hartato (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines non-compete clauses (NCCs) in franchise agreements within Indonesia’s legal framework, focusing on their alignment with antitrust laws and implications for market competition and entrepreneurship. By analyzing statutory provisions, judicial precedents, and doctrinal interpretations, this normative juridical research evaluates the proportionality and enforceability of NCCs under Indonesian contract and labor law. The study highlights the restrictive nature of NCCs, their potential to hinder economic mobility, and the challenges posed by the lack of regulatory clarity. Findings reveal that while NCCs safeguard franchisors’ interests, overly broad clauses risk violating constitutional principles. The research underscores the need for clear regulatory guidelines to balance contractual autonomy, fair market practices, and labor mobility, promoting innovation and sustainable growth.